Pop-Up Book Learning Media for Nationalism Character Building - Dewi, Sinta Maria; Sofyan, Davi; Priyono, Ali (International Journal of Elementary Education, 2022)
There are still many teachers who use handbooks as teaching materials, even during the Covid-19 pandemic, teachers only use the WhatsApp application as a medium to deliver material. This study aims to develop learning media in the form of a book called Pop-up Book using thick paper. Pop-up Book media development aims to build the character of nationalism in third and fourth grade elementary school students in social studies subjects. The method used in this study is a research and development (R&D) method that refers to the Borg and Gall model. The instruments used in this study were questionnaire sheets, interview sheets, and validation sheets. The type of the three assessment instruments is non-test. The data analysis technique used in this research is descriptive qualitative and quantitative data analysis techniques. The results showed that based on the results of the validation of the pop-up book media get a percentage of 97% with a very valid category. The validation of social studies material in the pop-up book gets a percentage of 86% with a very valid category. Validation Language pop-up book media get a percentage of 88% with a very valid category. Based on the results of the validation that has been carried out, the pop-up book media is declared very valid in developing the character of nationalism in social studies subjects for elementary school students. The limitation of this study is that we did not test the effectiveness of the pop-up book development model. The recommendation for further researchers is to test the effectiveness of this model, in order to obtain information that the pop-up book development model is feasible and effective to use for elementary school students.